Keabsahan Surat Peringatan sebagai Pengganti Akta Pengakuan Utang dalam Lelang Eksekusi Tanggungan - Rahardian Utama, Muhamad Adji; Hakim, Nur; Pandiangan, Roni (JIMLY LEGAL YUSTISIA JOURNAL, 2024)
The process of foreclosure under Indonesian law generally requires a debt acknowledgment deed as valid evidence of legal relationship between debtor and creditor. However, current practices show that warning letters are sometimes used as an alternative to the debt acknowledgment deed in some foreclosure cases. The issue raised in this study concerns the validity of using Warning Letter as substitution for Debt Acknowledgment Deed in the execution auction process of collateral rights in Indonesia. The Debt Acknowledgment Deed holds an important position in Indonesian law as a valid legal instrument that facilitates the execution against debtors who fail to repay their debts. Meanwhile, the Warning Letter is often used as an initial step in debt collection, but it does not carry the same legal force as the Debt Acknowledgment Deed. The purpose of this writing is to analyze the validity of using the Warning Letter as a substitute for the Debt Acknowledgment Deed in the execution auction procedure of collateral rights. The method used in this research is normative approach by analyzing the applicable regulations, jurisprudence, and relevant legal doctrines. The results of this research show that, although the Warning Letter plays an important role in the early stages of debt collection, it cannot replace the legal status of the Debt Acknowledgment Deed in the execution auction of collateral rights. Therefore, further regulation is needed regarding the use of the Warning Letter in the execution auction process of collateral rights to provide legal certainty for both parties, creditors and debtors.